Common good and the concept of expropriation in international law on foreign investment: Determinacy of substance in legitimacy of structure - Falsafi, Alireza (McGill University, 2011)
This thesis, exploring the rule of law for international rules, offers a human bond of common good between determinacy of substance and legitimacy of structure of rules in order to evaluate international obligations of States in international law on foreign investment. In an in-depth exposition of the theoretical underpinnings and practices underlying the normative structure of rules in international law, the thesis critically questions the legal reasoning embedded in—and the authority of rules borrowed from—principles and precedents or moral and political evaluations by arbitrators in interpretation of States' contractual, customary, and treaty obligations in investment arbitrations. With crucial moral, political, social and economic ramifications for the constitutional functions of States and concomitant interests of their human members implicated in the concept of expropriation in international law, the thesis provides a framework of legitimacy in a common good approach with structural criteria of recognition and coherence for the interpretation of States' obligations in investment arbitration. Coherence brings to the fore conflicting demands of justice requiring fresh evaluation divesting a general rule of its authoritative force, and recognition brings to the fore the validation of the power to engage in moral and political evaluation. Together, these structural criteria offer a common good approach of legitimacy to test the authority of States' obligations and the power of arbitrators in hard cases. By virtue of these criteria, the thesis characterizes the nature of substantive property rights of corporations and corresponding obligations of States in foreign investment as contingent and consensual in contrast with the absolute and constitutional rights of human beings in human rights. Through coherence and recognition, the thesis also portrays a supreme status for customary international law for the normative structure and substance of States' contractual or treaty obligations in the interpretation of hard cases in international law on foreign investment. The thesis espouses a new horizon for legal reasoning in foreign investment arbitration that eschews the lex lata veneer for lex ferenda propositions manufactured from precedents and principles, on the one hand, and the sheen of law for the conception of justice of investor-State arbitrators, on the other, in cases of hard confrontation between the demands of justice.
https://escholarship.mcgill.ca/concern/theses/dv13zz300
Keywords: Expropriation; Foreign investment; International law

Revisiting the Depoliticization of Investment Disputes - Schneiderman, David (Yearbook on International Investment Law and Policy, 2011)
The chapter challenges claims about depoliticization in two different aspects. The first examined claim is that home states are disenfranchised from pursuing investment claims once they are lodged with ICSID. Is it the case that home states simply stay home? This chapter examines instances where home states may have played a role in investment disputes between contracting states. What the record generally reveals, however, is that home states involve themselves in disputes where ICSID hearings are imminent but not yet in play. The second, broader, reading of depoliticization maintains that disputes now are resolved without recourse to lowly politics but to ‘higher’ law. This more extravagant claim is vulnerable to the critique that investor-state dispute resolution is not emptied of political content but, instead, spills over with politics. As the regime implicates the capacity of public authority to act in a wide variety of regulatory contexts, the separation of law from politics is hard to credibly maintain. Not only are investor-state disputes embedded within regimes of political discourse and political power, the ambit of investment arbitrator discretion is so capacious that it can be said of arbitrators, as it has been said of the U.S. Supreme Court, that they can sensibly be regarded as political actors.
Accepted: 2024-06-14T19:55:42Z

Essays on policy reforms in trade, investment and taxation - Wagle, Swarnim (Australian National University, 2011)
This thesis consists of three essays on trade, investment, and taxation that are unified by their policy relevance to developing countries. Following an introductory chapter on policy reform, the first essay revisits the institutional determinants of foreign direct investment (FDI) using a comprehensive new data set covering more than 80 countries. It exploits the presence of confirmed zero investment flows between countries to estimate productivity cut-offs of firms that invest abroad profitably. This approach corrects likely biases arising from firm heterogeneity and country selection in a theoretically derived gravity-type model. The analysis finds inward FDI to be highly responsive to cross-country variation in specific institutional provisions, such as arbitration of disputes and legal procedures to establish foreign subsidiaries. The importance of FDI-specific regulations stands out even after controlling for the general quality of institutions. Statutory openness to FDI, however, has no association with actual inflow of investment. The second essay examines cross-national differences in the survival of exports through the lenses of product, industry, and country characteristics. The estimates are derived from a new application of discrete-time models instead of the continuous-time (Cox) models that are standard in trade duration analysis. The examination of exports originating in more than 100 developing countries covering 4000 products over 12 years shows that export flows are much more fragile than suggested by trade theory. Using new measures of product sophistication and export diversification, the paper finds evidence of information and network externalities that aid export survival. Exports concentrated in a few industries or in a narrow range of destination markets exhibit higher rates of death, whereas export concentration within some industries is positively associated with survival, suggesting a synergistic network effect. The probability of export death decreases with proximity from the capital content of products to the national factor endowment, competitive real exchange rate, and bilateral trade preferences. Further, death rates for dynamic subsets of exports like manufactured components and processed food differ from other products, belying the notion that short durations are necessarily a result of poor exporter capabilities. The third essay assesses the revenue implications of coordinated tariff and tax reforms. It is shown for a sample of low-income countries over 25 years that they have had a mixed record of offsetting reductions in trade tax revenue, and that Value-Added Tax (VAT) has, at best, played a limited role. The paper then analyzes the specific case of Nepal, using a unique data set compiled from unpublished customs records of imports, tariffs, and all other taxes levied at the border. It estimates changes to revenue and domestic production associated with two sets of reforms: i) proportional tariff cuts coordinated with a strictly enforced VAT; and ii) proposed tariff cuts under a regional free trade agreement. It is shown that a revenue-neutral tax reform is conditional on the effectiveness with which domestic taxes are enforced. Furthermore, loss of revenue as a result of intra-regional free trade can be minimized through judicious use of Sensitive Lists that still cover "substantially all the trade" as required by Article XXIV of the General Agreement on Tariffs and Trade (GATT).
Keywords: Commercial policy; Fiscal policy; Free Trade; Investments; Taxation